2011
DOI: 10.1021/cm1029563
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Activation of CO2 by Amine-Modified Nanoporous Materials Studied by Solid-State NMR and 13CO2 Adsorption

Abstract: The interaction of gaseous CO 2 with the surface of amine-modified nanoporous clays has been studied. CO 2 adsorption and adsorption microcalorimetry revealed high adsorption capacity and strong interaction with the surface at low pressures, due to the presence of amine groups. Considerable surface heterogeneity and high initial adsorption heat (125 kJ mol -1 ) have been observed, although the adsorption was reversible with hysteresis at low pressures and very slow desorption kinetics. Interaction between 13 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
218
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(235 citation statements)
references
References 55 publications
11
218
0
6
Order By: Relevance
“…2B). As expected, no signal is detected around 125 ppm (28). Therefore, the NMR peak at 163.9 ppm arises from the carbon which is Solid data points represent gas adsorption and open points are gas desorption after a maximum pressure of ∼800 Torr.…”
Section: Significancesupporting
confidence: 65%
See 1 more Smart Citation
“…2B). As expected, no signal is detected around 125 ppm (28). Therefore, the NMR peak at 163.9 ppm arises from the carbon which is Solid data points represent gas adsorption and open points are gas desorption after a maximum pressure of ∼800 Torr.…”
Section: Significancesupporting
confidence: 65%
“…covalently bound to the fiber (28). Indeed, this peak should arise from the formation of carbamate through the reaction of carbon dioxide with the primary amino groups of lysine residues similar to that observed in the amine solutions (4).…”
Section: Significancementioning
confidence: 91%
“…CO 2 molecule can not combine with tertiary amino group in the absence of water [41]. Thus the theoretical maximum amino utilization efficiency of the branched PEI is about 35% [42][43][44]. The results in this study showed Yin et al -eXPRESS Polymer Letters Vol.11, No.11 (2017) 873-884 Figure 7.…”
Section: Co 2 Adsorption Performance Of Pei Supported On Pmfrsmentioning
confidence: 64%
“…The influence of temperature on the CO 2 adsorption of PMFR-PEI-30% (30% PEI loading) was investigated ( Figure 8). It is obvious that the PMFR-PEI-30% adsorbent showed a maximum adsorption capacity of 2.89 mmol/g at 30°C, implying the balance between CO 2 diffusion into inner layer of PEI and the desorption of CO 2 from PEI [43,45]. The adsorption process at a lower temperature was diffusion controlled, elevation of temperature would accelerate the diffusion of CO 2 inside of the thick layer of the PEI, and be beneficial for the full extension of the PEI's chain and hence provide more adsorption sites, leading to more sufficient contact with CO 2 .…”
Section: Co 2 Adsorption Performance Of Pei Supported On Pmfrsmentioning
confidence: 99%
“…(Figure 9). Moreover, an additional resonance at 164 ppm was clearly visible in all the samples and was attributed to the presence of carbamate groups 54 . Moore et.al has studied CO 2 adsorption on hyperbranched amine polymers grown from the mesoporous silica SBA--15 which exhibited mixture of chemisorption products, including carbamate, carbamic acid and bicarbonate moieties [55] .…”
Section: Study Of Reactivity Between Co 2 and Organo--modified Sba--15mentioning
confidence: 90%